Cryptococcemia Resulting in an Incomplete Abortion in an HIV-Positive Patient - Kurosh Rahimi; Runjan Chetty; Blaise Clarke (Canadian Journal of Infectious Diseases and Medical Microbiology)
Exotic infections and unusual presentations are the norm in immunocompromised patients. An unusual case of cryptococcemia resulting in a miscarriage is reported. This was the first presentation of the disease and the sentinel infection in the patient who was found to be HIV positive. Histological evaluation of the dilation and curettage specimen showed numerous typical organisms of cryptococcus present within the products of conception. There was a focal granulomatous response to the organisms. An accompanying cryptococcal endometritis was not noted. Other concomitant infections were not seen.